Collaboration between non-governmental organizations and public services in health – a qualitative case study from rural Ecuador. Issue 1 (1st December 2016) - Biermann, Olivia; Eckhardt, Martin; Carlfjord, Siw; Falk, Magnus; Forsberg, Birger C.
Abstract : Background: Non-governmental organizations (NGOs) have a key role in improving health in low- and middle-income countries. Their work needs to be synergistic, complementary to public services, and rooted in community mobilization and collective action. The study explores how an NGO and its health services are perceived by the population that it serves, and how it can contribute to reducing barriers to care. Design: A qualitative exploratory study was conducted in remote Ecuador, characterized by its widespread poverty and lack of official governance. An international NGO collaborated closely with the public services to deliver preventative and curative health services. Data were collected using focus group discussions and semistructured interviews with purposively sampled community members, healthcare personnel, and community health workers based on their links to the health services. Conventional qualitative content analysis was used, focusing on manifest content. Results: Emerging themes relate to the public private partnership (PPP), the NGO and its services, and community participation. The population perceives the NGO positively, linking it to healthcare improvements. Their priority is to get services, irrespective of the provider's structure. The presence of an NGO in the operation may contribute to unrealistic expectations of health services, affecting perceptions of the latter negatively. Conclusions: To avoid unrealistic expectations and dissatisfaction, and to increase and sustain the population's trust in the organization, an NGO should operate in a manner that is as integrated as possible within the existing structure. The NGO should work close to the population it serves, with services anchored in the community. PPP parties should develop a common platform with joint messages to the target population on the provider's structure, and regarding partners' roles and responsibilities. Interaction between the population and the providers on service content and their expectations is key to positive outcomes of PPP operations.